Parameterized design of abort trajectories with a lunar flyby for a crewed mission. Issue 6 (15th March 2023) - Dong, Tianshan; Luo, Qinqin; Han, Chao; Xu, Ming
Highlights: An analytical preliminary design method for abort trajectory with a lunar flyby is proposed based on pseudostate theory. Two parameters in the design process are taken as variables, then an ergodic representation of the feasible abort trajectories with a certain abort time is developed. The performances of these abort trajectories in an ergodic representation including duration time, injection propellant and re-entry points distribution are investigated. The effects of abort time and the nominal mission trajectory on abort trajectories are evaluated. Abstract: This article proposes an analytical preliminary design method for abort trajectory with a lunar flyby and the trajectory ergodic representation based on parameterization, as well as their application in studying the abort trajectories' characteristics. First, by introducing two parameters, the perilune altitude and the perilune transfer time, the preliminary solution is developed parametrically using pseudostate theory to connect two special Lambert processes. The fast convergence of the improved differential correction under the high-fidelity gravity field verifies the accuracy of the proposed preliminary design method. Next, the two parameters are regarded as a set of variables to define an abort trajectory. Based on this, an ergodic representation of the abort trajectory with a certain abort time is yielded using the proposed design method, which offers a global view of the feasible abort trajectories. In addition, the influences of some factors on the performance of these abort trajectories are investigated based on the proposed design method and ergodic representation. The simulation results show that the abort time and the transfer time of the nominal trajectory significantly affect the ergodic representation and characteristics of the abort trajectory.